Japanese Encephalitis can be devastating - Lopalco, Pier Luigi; Biasio, Luigi Roberto (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Japanese encephalitis, caused by the JE virus transmitted by mosquitoes, is the most common type of epidemic encephalitis in Asia. It is endemic in most of South and Southeast Asia, but the number of cases can vary greatly between areas. While many infections do not lead to disease, the symptomatic cases can be very severe and life-threatening. It mainly affects children, whereas adults are generally immune to the disease due to either being infected in childhood or receiving vaccination. However, individuals who are not immune, such as travelers from non-endemic countries, are susceptible to the disease when exposed to the virus for the first time, regardless of age. Without antiviral treatment options, vaccination is the only strategy to establish effective protection against Japanese encephalitis.